A interferência da prática de aulas de yoga - presencial e virtual - nos estados de ânimo de seus praticantes - Pinto, Ana Cláudia Gomes de Amorim [UNESP] (2015)
Three aspects motivated the development of this study: the growth in use of new technologies in the health field allied to the democratization of internet access; the growing popularization of Yoga practice; and the increase in problems related to emotional states of people in general. An increase in the number of virtual Yoga classes can be noticed, which contributes to the propagation and adherence to this practice. However, studies on the implications of this new tendency on a variety of contexts are still scarce. Therefore, this study investigates the interference of Yoga classes in the emotional states of its participants, comparing the virtual context to the in-person context. An online course platform was used to present the classes and evaluate the participants' emotional states, and an online social network was used to ease the communication between the researchers and the participants. In order to evaluate their mood changes, the participants answered the reduced and illustrated Emotional States List (LEA-RI) (VOLP, 2000) before and after both online and in-person classes. It was also analyzed, through a questionnaire, how the participants felt about the online classes and the virtual platform, so it was possible to measure the implications, advantages and disadvantages of this new class context. The moods' analyses results were all positives, with a higher number of changes in the in-person practice when compared to virtual practice. As the assessment of the analysis of virtual classes revealed that most participants had a good attitude about the virtual platform as well as the virtual classes, after performing the first access in the in-person classes, most of them had enough motivation to return to practice more classes. The participant's expectations and needs were satisfied, and the content of lessons and reviews were well valued. Despite any technical difficulties, the distance Yoga classes through the platform can ...